2021
DOI: 10.1088/1674-1056/abd7d8
|View full text |Cite
|
Sign up to set email alerts
|

Properties of B4C-TiB2 ceramics prepared by spark plasma sintering*

Abstract: By doping titanium hydride (TiH2) into boron carbide (B4C), a series of B4C + x wt% TiH2 (x = 0, 5, 10, 15, and 20) composite ceramics were obtained through spark plasma sintering (SPS). The effects of the sintering temperature and the amount of TiH2 additive on the microstructure, mechanical and electrical properties of the sintered B4C-TiB2 composite ceramics were investigated. Powder mixtures of B4C with 0–20 wt% TiH2 were heated from 1400 °C to 1800 °C for 20 min under 50 MPa. The results indicated that hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Strengthening phases (such as TiC and TiB 2 ) can offer the advantages of high hardness, excellent wear resistance, good thermal stability [15,16], and good wettability with IN625 alloy [17,18]. It was reported that adding TiC particles into the ultra-high-speed lasermelted IN625 coatings could significantly improve the wear resistance, but the TiC particles often showed an agglomeration effect, leading to the uniform distribution of the hardness and wear rate of the extreme high speed laser cladding coatings [19].…”
Section: Of 16mentioning
confidence: 99%
“…Strengthening phases (such as TiC and TiB 2 ) can offer the advantages of high hardness, excellent wear resistance, good thermal stability [15,16], and good wettability with IN625 alloy [17,18]. It was reported that adding TiC particles into the ultra-high-speed lasermelted IN625 coatings could significantly improve the wear resistance, but the TiC particles often showed an agglomeration effect, leading to the uniform distribution of the hardness and wear rate of the extreme high speed laser cladding coatings [19].…”
Section: Of 16mentioning
confidence: 99%
“…Thus far, researchers have carried out a large number of studies on B 4 C-TiB 2 ceramic. They have studied the influence of factors, such as relative density, grain size, and content of the toughening phase, on the toughness and hardness of B 4 C-TiB 2 ceramics through different methods, such as pressureless sintering, hot pressing sintering, and spark plasma sintering, and achieved fruitful research results [ 1 , 2 , 3 ]. At the same time, however, it is difficult to further improve this material.…”
Section: Introductionmentioning
confidence: 99%